New course in Protein Structures in Drug Research - Naur, Peter (Improving University Science Teaching and Learning, 2023)
This project describes my reflections on my involvement in the planning, execution and student evaluation of the one-day course: “Three-dimensional Protein Structures in Drug Research”. The course is part of the ULLA summer school for PhD students and since this was the first time the course ran I had a unique opportunity to influence the planning of the course. I was not formally responsible for organizing the course, however, the relevant person gladly gave me the chance to influence planning as much as I wanted to.